Perspektif Hukum dalam Perlindungan Hak Asasi Manusia terhadap Pengungsi (Refugees) dan Pencari Suaka (Asylum Seekers) di Indonesia Dalam Penanganan Pengungsi di Luar Negeri Pada Masa Pandemi Covid-19 - Ichsanoodin Mufty Muthahari; M Almudawar (Universitas Batanghari Jambi, 2022)
The form of a state is the basis of one of the state instruments whose threats originating from external to the state must be considered. With state security instruments originating from external threats, it is necessary to have cooperation from various state instruments, both institutions that are under the auspices of the executive, legislative and judicial tasks. One of the instruments of state institutions that have security and carry out these tasks is the Directorate General of Immigration, which apart from the services of Kei, Law Enforcement and Facilitator of Community Welfare Development, one of the functions referred to in the above discussion is the state. The legal basis held by Immigration is Law Number 6 of 2011 concerning Immigration and several other legal instruments for security and other supervision. The Directorate General of Immigration detected several other agencies related to the duties of state security instruments. The state problems that have occurred in Indonesia related to security lately are the presence of a population of Refugees and Asylum seekers in Indonesia, the largest number of Refugees (Refugees) in Indonesia are Refugees who come from Afghan citizens. The reason the country has many large-scale refugee movements is because the country has reached an internal conflict in their country, and there are many phenomena of human rights violations such as violence, and inequality against women which is a basis for the freedom of a person's rights. The State of Indonesia legally and legally does not handle problems against Refugees (Refugees) because the State of Indonesia does not have the 1951 convention and the 1962 Protocol in Geneva, Switzerland which intensively discusses the handling of Refugees which was adopted by the United Nations as a form of elaboration of the United Nations (UN) Charter. and the Universal Declaration of Human Rights, in which the agreement intends to address and address the problems of Refugees, whether from threats of violence, rebellion, murder for various reasons due to ethnicity, race, religion and other political interests.